Characterization of the complete mitochondrial genome of the Tianjun yak (Bos grunniens) - Guo, Xian (Mitochondrial DNA B Resour, 2019)
Tianjun yak (Bos grunniens) is a yak breed with strong adaptation to the high-elevation, cold and anoxic environments. Its complete mitochondrial genome is 16,323 bp long with an asymmetric base composition, and harbors the 37 typical mitochondrial genes and one noncoding control region. The PCGs are initiated with the typical ATA or ATG codons, and are terminated with TAA, TAG or the incomplete stop codon T––. Phylogenetic analysis suggests that Tianjun yak is most closely related to the polled yak.